Metabolic Pathways and Potencies of New Fentanyl Analogs - Wilde, Maurice; Pichini, Simona; Pacifici, Roberta; Tagliabracci, Adriano; Busardò, Francesco Paolo; Auwärter, Volker; Solimini, Renata (Frontiers in Pharmacology, 2019)
Up to now, little is known about the metabolic pathways of new fentanyl analogs that have recently emerged on the drug markets worldwide with high potential for producing addiction and severe adverse effects including coma and death. For some of the compound, limited information on the metabolism has been published, however, for others so far no information is available. Considering the well characterized metabolism of the pharmaceutically used opioid fentanyl and the so far available data, the metabolism of the new fentanyl analogs can be anticipated to generally involve reactions like hydrolysis, hydroxylation (and further oxidation steps), N- and O-dealkylation and O-methylation. Furthermore, phase II metabolic reactions can be expected comprising glucuronide or sulfate conjugate formation. When analyzing blood and urine samples of acute intoxication cases or fatalities, the presence of metabolites can be crucial for confirmation of the uptake of such compounds and further interpretation. Here we present a review on the metabolic profiles of new fentanyl analogs responsible for a growing number of severe and fatal intoxications in the United States, Europe, Canada, Australia, and Japan in the last years, as assessed by a systematic search of the scientific literature and official reports.